The question of access: Toward an equitable future of computational design. (December 2021) - Noel, Vernelle AA; Boeva, Yana; Dortdivanlioglu, Hayri
Digital fabrication and its cultivated spaces promise to break disciplinary boundaries and enable access to its technologies and computation for the broader public. This paper examines the trope of "access" in digital fabrication, design, and craft, and illustrates how it unfolds in these spaces and practices. An equitable future is one that builds on and creates space for multiple bodies, knowledges, and skills; allows perceptual interaction and corporeal engagement with people, materials, and tools; and employs technologies accessible to broad groups of society. By conducting comparative and transnational ethnographic studies at digital fabrication and crafting sites, and performing craft-centered computational design studies, we offer a critical description of what access looks like in an equitable future that includes digital fabrication. The study highlights the need to examine universal conceptions and study how they are operationalized in broader narratives and design pedagogy traditions.